Sosialisasi Pentingnya Menguasai Bahasa Inggris Bagi Mahasiswa - Thariq, Phoenna Ath; Husna, Asmaul; Aulia, Eza; Djusfi, Apri Rotin; Lestari, Rachmatika; Fahrimal, Yuhdi; Jhoanda, Rahmad (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
English is a language that has generally been used as a forum for communication with an international scope, so that English can be said to be universal, where its use is not only a communication bridge in everyday life in the international world but has also penetrated cyber communication. Especially in the current era of globalization, the very fast exchange of information related to scientific developments requires students to have proficiency in mastering English. English proficiency is not only a requirement for students to study abroad, but also for exploring more global knowledge, where available materials such as those in international journals are generally available in English. The problem that arises is that students are constrained in mastering English as a compulsory skill that must be possessed at this time. Therefore, this activity aims to motivate and provide awareness regarding the importance of mastering English among students. This activity was carried out at the FKIP Syiah Kuala University Auditorium which was attended by approximately 120 students. This activity aims to make students more motivated and motivated to hone their mastery of English, so that they have international insights and are useful as a tool to answer the challenges of scientific development in the era of globalization.